Exploring future inundation risk due to sea level rise using CMIP6 models in Indonesia - Pratiwi, Dwi Astuti Wahyu Wulan; Hiromune Yokoki (Teknisia, 2026)
Sea level rise (SLR) is one of the most significant impacts of climate change which threatening coastal areas, particularly in archipelagic countries like Indonesia. This study projects the extent of inundation, the number of at-risk populations, and estimates of damage cost due to SLR through 2100. The analysis was conducted by combining the projections of sea level (zos and zostoga) from five CMIP6 models: MIROC6, ACCESS-ESM1-5, CanESM5, NorESM2-MM and MRI-ESM2-0, elevation data from ETOPO2022, tides from TPXO10, and population data from NCAR and IIASA. The estimated damage cost was calculated using a regression model based on historical disaster data from EM-DAT. The findings of the analysis indicate that, without mitigation and adaptation measures, Indonesia could experience permanent inundation of 18,700 to over 39,500 km² with an affected population of around 10 million in 2100. National damage cost due to SLR is projected to reach USD 7 billion in 2050 and increase to USD 10 billion in 2100 in high emission scenario. The provinces with the highest physical impact are South Kalimantan and South Sumatra, highest social impact and damage cost occur in East Java and South Kalimantan. These findings emphasize that climate change mitigation and adaptation policies in Indonesia must be planned equitably and supported by robust projections.